Organic or Inorganic Nitrogen and Rhizobia Inoculation Provide Synergistic Growth Response of a Leguminous Forb and Tree - Zhang, Peng; Dumroese, R. Kasten; Pinto, Jeremiah R. (Frontiers in Plant Science, 2019)
Our objective was to better understand how organic and inorganic nitrogen (N) forms supplied to a tree, Robinia pseudoacacia, and a perennial forb, Lupinus latifolius, affected plant growth and performance of their symbiotic, N-fixing rhizobia. In one experiment, we tested five sources of N [none; three inorganic forms (ammonium, nitrate, ammonium-nitrate); and an organic form (arginine)] in combination with or without rhizobia inoculation. We measured seedling morphology, allometry, nodule biomass, and N status. A second experiment explored combinations of supplied 15N and inoculation to examine if inorganic or organic N was deleterious to nodule N-fixation. Plant growth was similar among N forms. A positive response of nodule biomass to N was greater in Robinia than Lupinus. For Robinia, inorganic ammonium promoted more nodule biomass than organic arginine. N-fixation was concurrent with robust supply of either inorganic or organic N, and N supply and inoculation significantly interacted to enhance growth of Robinia. For Lupinus, the main effects of inoculation and N supply increased growth but no interaction was observed. Our results indicate that these important restoration species for forest ecosystems respond well to organic or inorganic N forms (or various forms of inorganic N), suggest that the nodulation response may depend on plant species, and show that, in terms of plant growth, N supply and nodulation can be synergistic.